2021
DOI: 10.31020/mutftd.752988
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Education Given to Patients with Diabetes in Line with Health Belief Model on Their Health Belief, Perception of Self-Efficacy and Decision Making Level

Abstract: Amaç: Bu araştırma diyabet hastalarına Sağlık İnanç Modeli doğrultusunda verilen eğitimin hastaların sağlık inancına, öz etkililik algısına ve karar verme düzeyine etkisini belirlemek amacıyla yapılmıştır.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 7 publications
(12 reference statements)
1
6
1
2
Order By: Relevance
“…In our study, no significant association was found between monitoring of blood glucose and self-efficacy; however, in previous studies it was observed that self-efficacy level was higher in patients who respond positively to the question of presence or absence of regular health control [16,19]. In line with our study, in various studies no association was found between smoking and self-efficacy [15,17,18]. In our study, self-efficacy score of patients getting diabetes education was somewhat higher but the difference wasn't statistically significant.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…In our study, no significant association was found between monitoring of blood glucose and self-efficacy; however, in previous studies it was observed that self-efficacy level was higher in patients who respond positively to the question of presence or absence of regular health control [16,19]. In line with our study, in various studies no association was found between smoking and self-efficacy [15,17,18]. In our study, self-efficacy score of patients getting diabetes education was somewhat higher but the difference wasn't statistically significant.…”
Section: Discussionsupporting
confidence: 87%
“…Association between insulin use and self-efficacy is another area with conflicting results in the literature. There was no clear association [16][17][18][19]. In the studies usually no association was found between HbA1c level and self-efficacy [15,18].…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations